SOSIALISASI STANDAR FASILITAS TEMPAT PENGOLAHAN SAMPAH REDUCE-REUSE-RECYCLE KSM SRIMENANTI JAYA, SUNGAILIAT, BANGKA - Andina Syafrina; Rizka Felly; Helfa Rahmadyani (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
The increase in the volume of waste from day to day is a problem that can threaten environmental sustainability. The increase in the volume of waste can be triggered by the low level of awareness and awareness of the community regarding good waste management methods. Increasing public awareness can be done through waste management education activities, so it needs to be supported by adequate waste management facilities. The identification carried out on the waste management facilities at TPS 3R Srimenanti Jaya was not in accordance with the standards set by the Directorate General of Human Settlements Number 03 of 2020 concerning the Implementation of Waste Infrastructure and Facilities in Handling Household Waste and Types of Household Waste. The socialization was carried out in the form of presentations containing standard material for 3R TPS facilities and examples of good 3R TPS designs to the Srimenanti Jaya TPS 3R managers. The socialization activity was carried out well and received support from the 3R TPS manager to follow up on activities to improve the Srimenanti Jaya 3R TPS management facility so that it meets standards and can attract people's interest to learn about waste management.